2016
DOI: 10.1080/20786190.2016.1186366
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of unprofessional conduct by medical practitioners in South Africa (2007–2013)1

Abstract: A role of ethics in the medical context is to protect the interests, freedoms and well-being of patients. A critical analysis of unprofessional conduct by medical practitioners registered with the Health Professions Council of South Africa (HPCSA) requires a better understanding of the specific ethics misconduct trends. To investigate the objectives the case content and sanctions of all guilty decisions related to unprofessional conduct against HPCSA-registered medical practitioners in the period 2007 to 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Such fraudulent conduct constitutes a contravention of the HPCSA's Ethical and Professional Rules, specifically section 7(5) that deals with fees and commission (HPCSA 2008 ). The relative frequency of fraudulent-related transgressions in relation to all ethical transgressions for physiotherapists in this study is higher than what was found for other health practitioners in South Africa during the same period (2007–2013): dentists (55%) (Nortjé & Hoffmann 2014 ), medical practitioners (48.4%) (Hoffmann & Nortjé in press ) and psychologists (21%) (Nortjé & Hoffmann 2015 ). These findings support the opinion of Ogubanjo and Knapp van Bogaert ( 2014 ) that health care fraud is a serious ethical issue for many health care practitioners in South Africa, especially as this type of fraudulent personal gain behaviour almost always results in direct or indirect prejudice to the patient and medical aid scheme.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Such fraudulent conduct constitutes a contravention of the HPCSA's Ethical and Professional Rules, specifically section 7(5) that deals with fees and commission (HPCSA 2008 ). The relative frequency of fraudulent-related transgressions in relation to all ethical transgressions for physiotherapists in this study is higher than what was found for other health practitioners in South Africa during the same period (2007–2013): dentists (55%) (Nortjé & Hoffmann 2014 ), medical practitioners (48.4%) (Hoffmann & Nortjé in press ) and psychologists (21%) (Nortjé & Hoffmann 2015 ). These findings support the opinion of Ogubanjo and Knapp van Bogaert ( 2014 ) that health care fraud is a serious ethical issue for many health care practitioners in South Africa, especially as this type of fraudulent personal gain behaviour almost always results in direct or indirect prejudice to the patient and medical aid scheme.…”
Section: Discussioncontrasting
confidence: 66%
“…In some of the cases involving issuing misleading, inaccurate and/or false statements, or failure to obtain patient consent to perform procedures or interventions, or making derogatory /abusive remarks towards a patient, the sanctioned physiotherapists were ordered to attend a practice management course (7.4%, n = 2) or to attend a medical ethics and law course (7.4%, n = 2) ( Table 3 ). This is substantially higher than the 1.10% ( n = 5) of sanctioned medical practitioners in South Africa who were required to attend a medical ethics course in the period 2007–2013 (Hoffmann & Nortjé in press ); however, the low numbers of actual cases for physiotherapists ( n = 2) and medical practitioners ( n = 5) respectively in this regard indicate that any statistical interpretation should be approached with caution to avoid undue bias. The various penalties imposed to physiotherapists by the HPCSA indicate that the following transgressions are viewed as serious ethical misconduct: issuing misleading, inaccurate and/or false medical statements; false and/or inaccurate medical aid claims involving non-rendered services; over-servicing patients by performing redundant procedures; and failure to obtain patient consent to perform procedures and interventions, especially when it involves risks and potential complications.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Unethical behavior can be the result of a lack of ethics knowledge; however, in many cases, despite ethics knowledge, professionals engage in unethical behaviors or reasoning. [ 29 30 31 32 ]…”
Section: Discussionmentioning
confidence: 99%